1992
DOI: 10.1007/bf02035128
|View full text |Cite
|
Sign up to set email alerts
|

Possible direct role of reactive oxygens in the cause of cutaneous phototoxicity induced by five quinolones in mice

Abstract: The mechanisms of phototoxicity induced in mice by five quinolone antibacterial agents were investigated using mouse 3T3 fibroblast cells and Balb/c mice. In the in vitro study, the cultured cells were exposed to ultraviolet-A (UVA) in the presence of the five quinolones lomefloxacin, enoxacin, ciprofloxacin, ofloxacin and DR-3355 (the s-isomer of ofloxacin). Cytotoxicity after irradiation was assayed by the neutral red and MTT assay methods, both of which revealed dose-dependent phototoxicity for all five qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…In this context, the membrane damage monitored by lipid peroxidation and protein cross-link seems to confirm this hypothesis. These data are in good agreement with the data reported by Wagai and Tawara [6] [7], who have demonstrated that the phototoxicity associated with quinolones in balb/c mice was initiated by the generation of ROS in the target tissue, which specifically involved hydroxyl radical, as well superoxide anion and hydrogen peroxide. Moreover, it has also been reported that the initial steps in the quinolone phototoxicity probably involve hydroxyl-radical attack on the cell membrane and mitochondria [32].…”
supporting
confidence: 94%
“…In this context, the membrane damage monitored by lipid peroxidation and protein cross-link seems to confirm this hypothesis. These data are in good agreement with the data reported by Wagai and Tawara [6] [7], who have demonstrated that the phototoxicity associated with quinolones in balb/c mice was initiated by the generation of ROS in the target tissue, which specifically involved hydroxyl radical, as well superoxide anion and hydrogen peroxide. Moreover, it has also been reported that the initial steps in the quinolone phototoxicity probably involve hydroxyl-radical attack on the cell membrane and mitochondria [32].…”
supporting
confidence: 94%
“…Furthermore, a-tocopherol acetate supplementation reduced enrofloxacin residues in turkey meat, which indicate a possible interaction between both molecules that reduces the amount of enrofloxacin in tissues [4,25]. Studies on phototoxic actions of fluoroquinolones revealed that these toxic effects are related to induction of reactive oxygen species [12,23,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 95%
“…The action of these photosensitizers is dependent on the production of extremely reactive molecular species (reactive oxygen species, free radicals, photoproducts), able to modify the cell components, including lipids, proteins and nucleic acids, in combination with UVA; it has been suggested that the most phototoxic quinolones are those that induce the formation of reactive oxygen species (ROS), because these species cause severe tissue damages [6][7][8] . However, a correlation between the production of ROS and the phototoxic potency of fluoroquinolones cannot be drawn and other mechanisms, i.e.…”
Section: Introductionmentioning
confidence: 99%